The Mindful Brain and Emotion Regulation in Mood Disorders - Farb, Norman A. S. (2012)
Mindfulness involves nonjudgmental attention to present-moment experience. In its therapeutic forms, mindfulness interventions promote increased tolerance of negative affect and improved well being. However, the neural mechanisms underlying mindful mood regulation are poorly understood. Mindfulness training appears to enhance attentional monitoring systems in the brain, supported by the anterior cingulate and lateral prefrontal cortices. In emotion regulation, this prefrontal training seems to promote the stable recruitment of a non-conceptual sensory pathway, an alternative to conventional cognitive reappraisal strategies. In neural terms, the transition to non-conceptual awareness involves reducing habitual evaluative processing supported by midline structures of the prefrontal cortex. Instead, attentional resources are directed towards a limbic pathway for present-moment sensory awareness, involving the thalamus, insula, and primary sensory regions. In patients with affective disorders, mindfulness training acts as an alternative to cognitive efforts to control emotion, instead directing attention towards broadly monitoring fluctuations in momentary experience. Limiting cognitive elaboration in favor of momentary awareness appears to reduce automatic negative self-evaluation, increase tolerance for negative affect and pain, and help to engender self-compassion and empathy in chronically dysphoric individuals.